Adaptasi Kurikulum Pembelajaran IPA Di Sekolah Inklusif SDN Gajahmungkur 02 Kota Semarang - Widiyawati, Yeni; Khasanah, Malikhatun; Farhatin, Aulia Hanna (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The inclusive education program is an effort to carry out the mandate of the 1945 Constitution and eliminate discrimination in the education system in Indonesia. All children with various needs can sit and study together with other normal children in the same school. This study aims to identify forms of curriculum adaptation, especially in science subjects at SDN Gajahmungkur 02 Semarang City. This research uses a descriptive-qualitative approach with a case study method. This research was conducted in April-June 2022. The data collection technique used in this study used interviews and observation methods. The subject of the interview is a special supervising teacher at the school. Based on the results of interviews and observations, it is known that the curriculum adaptation implemented at SD N Gajahmungkur is viewed from the principles and dimensions of adaptation. The principles of attendance, participation, and achievement have been well realized in this school. In terms of the dimensions of curriculum adaptation, namely, curricular adaptation is reflected in the lesson plans accompanied by special notes and adjustment of learning indicators for children with special needs who are adapted to the 2013 curriculum, learning adaptation is reflected in the presence of a special supervisor teacher in the class even though there is only one. There is a special schedule arrangement so that Class teachers still have a significant role in implementing learning. Environmental adaptation has not been optimal because schools do not yet have accessibility for physically disabled people with wheelchairs. In terms of adjustment to science subjects, teachers have not made many adaptations or modifications for children with special needs.